O embate modernidade/pós-modernidade e seu impacto sobre a teoria e a prática educacionais - Pedro Goergen (EccoS – Revista Científica)
This article seeks to examine the relationship between the debate about modernity/ post-modernity and education. Mark at first, some central aspects of modernity and, as a result of post-modernity, by setting, from there a relationship between the theory and educational practice. The author keeps back, especially epistemological and ethical points of view, aiming to show the importance of changes in these fields that interfere in researches and educational activities.